Multiple Drivers of Local (Non-) Compliance in Community-Based Marine Resource Management: Case Studies from the South Pacific - Rohe, Janne R.; Aswani, Shankar; Schlüter, Achim; Ferse, Sebastian C. A. (Frontiers in Marine Science, 2017)
The outcomes of marine conservation and related management interventions depend to a large extent on people’s compliance with these rule systems. In the South Pacific, community-based marine resource management (CBMRM) has gained wide recognition as a strategy for the sustainable management of marine resources. In current practice, CBMRM initiatives often build upon customary forms of marine governance, integrating scientific advice and management principles in collaboration with external partners. However, diverse socio-economic developments as well as limited legal mandates can challenge these approaches. Compliance with and effective (legally-backed) enforcement of local management strategies constitute a growing challenge for communities - often resulting in considerable impact on the success or failure of CBMRM. Marine management arrangements are highly dynamic over time, and similarly compliance with rule systems tends to change depending on context. Understanding the factors contributing to (non-) compliance in a given setting is key to the design and function of adaptive management approaches. Yet, few empirical studies have looked in depth into the dynamics around local (non-) compliance with local marine tenure rules under the transforming management arrangements. Using two case studies from Solomon Islands and Fiji, we investigate what drives local (non-) compliance with CBMRM and what hinders or supports its effective enforcement. The case studies reveal that non-compliance is mainly driven by: (1) diminishing perceived legitimacy of local rules and rule-makers; (2) increased incentives to break rules due to market access and/ or lack of alternative income; and (3) relatively weak enforcement of local rules (i.e., low perceptions of risk from sanctions for rule-breaking). These drivers do not stand alone but can act together and add up to impair effective management. We further analyze how enforcement of CBMRM is challenged through a range of institutional; socio-cultural and technical/ financial constraints, which are in parts a result of the dynamism and ongoing transformations of management arrangements. Our study underlines the importance of better understanding and contextualizing marine resource management processes under dynamic conditions for an improved understanding of compliance in a particular setting.